2016
DOI: 10.1021/acs.organomet.6b00503
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Mechanism of Tandem Oxidative Acetoxylation/Ortho C–H Activation/Carbocyclization Catalyzed by Pd(OAc)2

Abstract: A density functional theory (DFT) study has been conducted to unveil the mechanisms of tandem oxidative acetoxylation/ortho C−H activation/ carbocyclization catalyzed by Pd(OAc) 2 . The potential competitive reaction pathways between oxidative acetoxylation and ortho C−H activation, C−H activation with outer-sphere and inner-sphere acetate ligands, and the role of DMSO in the reaction have been discussed in detail. The calculated results indicate that the oxidative acetoxylation proceeds before ortho C−H activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…The potential energy surface of the reaction was explored at the PCM­(AcOH)/ωB97XD/6-31G­(d,p),Lanl2DZ level of theory, taking into account solvation effects and dispersion interactions . Similar levels of theory have recently been applied to various problems in Pd-based C–H bond activation. Energies of the resulting stationary points were additionally evaluated using SMD­(AcOH)/M06/6-311++G­(d,p),SDD, for comparison with other recent computational work on Pd-induced reactivity. , The potential energy surface is made more complex by the conformational flexibility of the intermediates, which involves torsional degrees of freedom within the dipyrrolylmethane and around the Pd center. Intrinsic reaction coordinate (IRC) analyses performed for the bond-forming transition states and restricted conformational searches performed for local energy minima showed that the entire reaction path likely involves conformational rearrangement of intermediates at several stages.…”
Section: Resultsmentioning
confidence: 99%
“…The potential energy surface of the reaction was explored at the PCM­(AcOH)/ωB97XD/6-31G­(d,p),Lanl2DZ level of theory, taking into account solvation effects and dispersion interactions . Similar levels of theory have recently been applied to various problems in Pd-based C–H bond activation. Energies of the resulting stationary points were additionally evaluated using SMD­(AcOH)/M06/6-311++G­(d,p),SDD, for comparison with other recent computational work on Pd-induced reactivity. , The potential energy surface is made more complex by the conformational flexibility of the intermediates, which involves torsional degrees of freedom within the dipyrrolylmethane and around the Pd center. Intrinsic reaction coordinate (IRC) analyses performed for the bond-forming transition states and restricted conformational searches performed for local energy minima showed that the entire reaction path likely involves conformational rearrangement of intermediates at several stages.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with previous computational studies on borylation reactions catalyzed by transition-metal complexes, all calculations were carried out by the DFT method with the ωB97X-D method using the Gaussian 09 program . In the geometry optimization, the SDD basis set is used for the Ir center and 6-311G­(d,p) , basis sets are used for all of the other atoms .…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with our previous computational studies, 3,19,[50][51][52][53][54][55] all calculations in this study were carried out using the DFT method with uB97X-D 56 using the Gaussian 09 program. 57 The SMD polarizable continuum model in water as the solvent was employed in the calculations.…”
Section: Methodsmentioning
confidence: 99%